Wear behavior and mechanical properties of al-based FGM - Mahli, Maximus Kohnizio (2021)
The wear and mechanical properties of Aluminium, Al LM6 and Al/SiC Functionally Graded Material (FGM) which are produced by using horizontal centrifugal casting method have been studied. Two casting parameters with three different level are selected to produce the hollow cylinder namely pouring temperature (690, 710 and 725°C) and motor speed (1300, 1500 and 1700rpm). Taguchi method is used in the analysis to screen all the variables that have significant effects on the wear rate and mechanical properties of Al-based FGM. Furthermore, the optimization of Response Surface Methodology (RSM) is utilized to acquire a model that predict the optimum process parameter. The result indicates that the influencing parameter are load and type of material, and the best wear samples for this level of parameters are Al/SiC with pouring temperature of 725°C, motor speed of 1500 rpm, load of 10 N and sliding velocity of 1 m/s. Meanwhile, types of material are the most influencing parameter for hardness and strength analysis. Graded properties of Al-based FGM are observed from inner towards the outer periphery of the sample. The size of Si is bigger and concentrated at the inner periphery while SiC particles segregate towards the outer periphery due to its high density compared with Aluminium. Results revealed that all composites casted have the best hardness, strength and wear resistance at the outer periphery of the hollow cylinder.